ASYMMETRICAL COMPLEXATION AND SIMULTANEOUS ELECTROCHEMICAL RECOGNITION OF 2 DIFFERENT GROUP 2 METAL-CATIONS BY A 1,1'-FERROCENE-BIS(METHYLENE AZA-18-CROWN-6) RECEPTOR - Chen, Z; Pilgrim, A; Beer, P (1995)
Voltammetric (CV, SWV) and fast atom bombardment mass spectrometric evidence demonstrates for the first time that a 1,1′-ferrocene-bis(methylene aza-18-crown-6) receptor (L) is capable of asymmetrically complexing and electrochemically recognising two different Group 2 metal cations (Ba2+, Mg2+) simultaneously in acetonitrile solution.